Fulfillment of Human Rights for the Baduy Indigenous Community - Ahmad Rayhan; Raihan Indra Widjaya; Adinda Pramesty Sulistya; Mariatul Adawiyah Sopandi (Digital Press Social Sciences and Humanities)
Fulfillment of Human Rights (HAM) in the Baduy, a complex community in Lebak, Banten, faces a variety of complex challenges, including preserving traditional values, utilizing modern technology, and addressing issues related to education, health, and rights. -right of expression. This research aims to analyze Human Rights (HAM) in Baduy society using secondary research methods based on library data. The results show that cultural isolation, legal tensions, modernization, and development, as well as discrimination and stereotypes, significantly affect population human rights. This research explores the concept of Human Rights (HAM) as a fundamental ethical principle that encourages individual interaction and communication, emphasizing its universal application in contemporary society. This study highlights the need for universal protection and intervention in various challenging situations, as Human Rights for Indigenous Peoples, especially Baduy Community. This research also explores the unique identity of the Baduy people in Indonesia, their adherence to traditional norms, and the role of the government in upholding their rights. Customary law is law derived from the norms of daily life and manifested by the culture of native Indonesians. The understanding of human rights of the Baduy indigenous people is unique and closely tied to culture and customs. The government has an important role in preserving the Baduy traditional community